The effects of mobile phones on the study habits of UPV senior students - Clamano, Anabel P.; Dema-ala, Marivic; Espino, Gertie Joy P.; Pallada, Olga A.; Tanaleon, Moriel B. (2003.)
Mobile phones are very popular with young people and have obvious attraction for personal security and keeping in touch with others. Aware of the rampant use of mobile phones by students, the group investigated "The effects of Mobile Phones on the Study habits of UPV Senior Students. A total of sixty (60) students as respondents. Thirty (30) of the respondents have mobile phones and the other thirty (30) do not have mobile phones. The group decided to have respondents whom have mobile phones and do not have in order to compare the results regarding the standard of study habits of students. The researchers therefore concluded that mobile phones do not greatly affect the study habits of students. It is the student responsibility on how to balance their time between studying and engaging in new products of technologies. The researchers recommend further analysis and investigation.
Research Paper (Mgt 199-Management Research). -- [Iloilo City] : University of the Philippines in the Visayas-College of Management, March 24, 2003.